PROBLEMS AND PROSPECT OF THE IMPLEMENTATION OF COMPOSITE MATERIALS INTO THE FUEL SYSTEMS OF AIRCRAFTS - Shatylo, Serhii (Problems of Friction and Wear, 2025)
An overview of the current state of the implementation of composite materials into the structure of aircraft is provided, and the problems of using such materials in fuel systems, related to their requirements, as well as factors and phenomena occurring in such systems are given. Main requirements, according to the 25th chapter of aviation regulations are described, as well as factors that affect the performance of fuel systems, such as atmospheric pressure, temperature, humidity, etc. Presented multiple researches that highlights the issue of wear resistance of fuel systems, methods of researching friction and wear processes in metal and fuel pairs are described. A separate paragraph examines the interaction of composite polymer materials with aviation fuel from the point of view of strength, the phenomena provided by such interaction are described. The problems and prospects of future research on the tribopair of polymer composite material and aviation fuel are outlined.